Semantic web technologies research and applications - Patel, Archana; Debnath, Narayan C.; Bhushan, Bharat 1989- (CRC Press, 2023)
"Semantic web technologies (SWTs) offer the richest machine-interpretable (rather than just machine-processable) and explicit semantics that are being extensively used in various domains and industries. This book provides a roadmap for Semantic Web Technologies (SWTs) and highlights their role in wide range of domains including Cloud Computing, Internet of Things, Big data, Sensor Network, and so forth. It also explores the prospects of these technologies including different data interchange formats, query languages, ontologies, Linked Data, and notations. The role of SWTs in 'Epidemic Covid-19', 'E-Learning platforms and systems', 'Block chain', 'Open online courses', and 'Visual analytics in Healthcare' is described as well. Explores all the critical aspects of semantic web technologies (SWT) Discusses impact of SWTs on cloud computing, Internet of things, big data, and sensor network Offers a comprehensive examination of the emerging research in the areas of SWTs and their related domains Provides a template to develop a wide range of smart and intelligent applications Includes latest applications and examples with real data This book is aimed at Researchers and graduate students in Computer Science, Informatics, Web Technology, Cloud Computing, and Internet of Things"--
Includes bibliographical references and index
Keywords: Semantic Web